2006
DOI: 10.4028/www.scientific.net/msf.522-523.171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Content on the Oxidation Behaviour of High-Speed Steels under Dry and Moist Air Environments

Abstract: Development and use of high-speed steels for manufacturing the roll outer shell of hot strip mills represented a major recent technological advancement in the hot rolling field. However, it was observed that the oxidation behavior of these steels was different from that of conventional rolls. The high-speed steel oxidation rate is about four times higher than the alloys previously used. Furthermore, the rolling conditions are quite aggressive. Contact of the roll with the hot strip, air and water of the coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…Of particular note are the conditions for the micro beam analysis of the carbide composition. Our findings, indicating that chromium is uniformly distributed whereas molybdenum showed worst uniformity, have been confirmed also concerning the results obtained for other steel alloys, with the supporting data given in [13,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Of particular note are the conditions for the micro beam analysis of the carbide composition. Our findings, indicating that chromium is uniformly distributed whereas molybdenum showed worst uniformity, have been confirmed also concerning the results obtained for other steel alloys, with the supporting data given in [13,[17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 78%
“…Prolonged low-temperature gas-phase carburization of AISI 316L-type austenitic stainless steel can cause intragranular precipitation of the carbide M 7 C 3 (M: randomly dispersed Fe, Cr, Ni); the effect was observed by Ernst et al [16] . Effect of chromium content on the oxidation behaviour of high-speed steels under dry and moist air environments was studied by Monteiro and Rizzo [17]. Compositional changes in carbide M 7 C 3 upon annealing and the effect of Cr content on microstructure and properties of medium-alloy high carbon tool and die steel were studied by Palcut et al [18], and Zhang et al [19], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [43,44] have compared the oxidation rate of a HSS material at different temperatures and they have concluded that the matrix was easier than the carbides to be oxidized at low temperatures. However, their conclusions obviously contradict with the results shown in [37][38][39][40]45]. In addition, Yin et al [46] have recently reported that the HSS oxide scale thickness was as large as 5 μm after 2 hours oxidations below 600 °C.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…For example, Kim et al [37] have reported a significant influence of alloy elements vanadium (V) and chromium (Cr) by oxidizing three different HSS materials at 600°C. More details can be found in [38][39][40], where Cr-rich M 7 C 3 carbide had the best oxidation resistance than carbides MC and M 2 C because it dissolved high amount of chromium. Those observations were confirmed by the recent studies [41,42] by analyzing the morphology and microstructure evolutions of oxidized HSS samples.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many investigators were dealing with the study of structure and chemical composition of chromium-iron carbides [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The main aim of this work, with the results presented herewith, was to establish the behavior of chromium, molybdenum and vanadium in M 7 C 3 carbides occurring in NC11LV (160H12MF) steel austenitized at 1150 ºC.…”
Section: Introductionmentioning
confidence: 99%